The large bakery company in Colombia: An analysis of its accounting and residual profit (2017-2021) - Rivera Godoy, Jorge Alberto (Universidad Francisco de Paula Santander, 2024)
The objective of this research is to analyze the accounting and residual profit to know the financial performance of the large bakery company in Colombia in the period 2017-2021, following as methodology the analysis of trends of indicators that measure its efficiency in the use of assets, the efficacy in the control of costs and expenses and the effectiveness in the achievement of profits, and comparing them with the indicators of the related company in Europe. It is found that the large Colombian bakery company achieves returns on equity each year with the same orientation of the net profit margin, but less like its asset turnover and financial leverage; similar results were presented in the European company, although with higher values, except for the financial multiplier. In addition, the large Colombian bakery company created on average a percentage of residual profit, like its European counterpart, but surpassed by the latter.  The disadvantage with respect to the European company is due to its lower efficiency and efficacy, and the use of financial resources at a higher cost. Research could be extended for homogeneous groups in terms of age, life cycle stages, legal structure, and international trade.